The Effect of Service Quality and Facilities on the Satisfaction of PNM Employee Gathering Participants in the Siantar 1 Regional Event 2025 - Simbolon, Heri Bertus; Tarigan, Jenny Sari (Journal of Economics and Social Sciences (JESS), 2025)
The MICE (Meeting, Incentive, Convention, Exhibition) industry in Indonesia is experiencing rapid development, along with the increasing needs of companies in organizing internal activities such as employee gatherings. This research is motivated by the importance of participant satisfaction as an indicator of event success, especially at the PNM Employee Gathering Regional Siantar 1 Year 2025 event organized by Matakail Communication. The purpose of this study was to determine how much influence the quality of service and facilities on participant satisfaction in the event. This research uses quantitative methods with an associative approach. The sample amounted to 100 respondents from a total population of 790 gathering participants, who were taken using accidental sampling technique. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression, t test, F test, and coefficient of determination (R²). The results showed that partially, the quality of service and facilities had a significant effect partially on participant satisfaction. Simultaneously, both variables have a positive and significant effect on participant satisfaction, with an Fcount value of 172.101> Ftable 3.09 and significance <0.001. The coefficient of determination (R²) value of 77.6% indicates that 77.6% of variations in participant satisfaction are explained by service quality and facilities, the remaining 24.4% are influenced by other factors not examined in this study.